Perspectives on the diagnosis and management of functional cognitive disorder: An international Delphi study - Cabreira, V; Alty, J; Antic, S; Araújo, R; Aybek, S; Ball, HA; Baslet, G; Bhome, R; Coebergh, J; Dubois, B; Edwards, M; Filipović, SR; et al. (Wiley Open Access, 2024)
Background: Current proposed criteria for functional cognitive disorder (FCD) have not been externally validated. We sought to analyse the current perspectives of cognitive specialists in the diagnosis and management of FCD in comparison with neurodegenerative conditions. Methods: International experts in cognitive disorders were invited to assess seven illustrative clinical vignettes containing history and bedside characteristics alone. Participants assigned a probable diagnosis and selected the appropriate investigation and treatment. Qualitative, quantitative and inter‐rater agreement analyses were undertaken. Results: Eighteen diagnostic terminologies were assigned by 45 cognitive experts from 12 countries with a median of 13 years of experience, across the seven scenarios. Accurate discrimination between FCD and neurodegeneration was observed, independently of background and years of experience: 100% of the neurodegenerative vignettes were correctly classified and 75%–88% of the FCD diagnoses were attributed to non‐neurodegenerative causes. There was <50% agreement in the terminology used for FCD, in comparison with 87%–92% agreement for neurodegenerative syndromes. Blood tests and neuropsychological evaluation were the leading diagnostic modalities for FCD. Diagnostic communication, psychotherapy and psychiatry referral were the main suggested management strategies in FCD. Conclusions: Our study demonstrates the feasibility of distinguishing between FCD and neurodegeneration based on relevant patient characteristics and history details. These characteristics need further validation and operationalisation. Heterogeneous labelling and framing pose clinical and research challenges reflecting a lack of agreement in the field. Careful consideration of FCD diagnosis is advised, particularly in the presence of comorbidities. This study informs future research on diagnostic tools and evidence‐based interventions.